2017
DOI: 10.1186/s12934-017-0775-9
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the bioflocculant production and identifying the effect of overexpressing epsB on the synthesis of polysaccharide and γ-PGA in Bacillus licheniformis

Abstract: BackgroundPolysaccharides and poly-γ-glutamic acid (γ-PGA) are biomacromolecules that have been reported as bioflocculants, and they exhibit high flocculating activity in many industrial applications. Bacillus licheniformis CGMCC 2876 can produce polysaccharide and γ-PGA bioflocculants under different culture conditions. Several key genes are involved in the metabolic pathway of polysaccharides in B. licheniformis, but the impacts of the regulation of these genes on the production of polysaccharide biofloccula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In our previous study, we found that B. licheniformis CGMCC 2876 could produce polysaccharides and γ-PGA under different culture conditions [ 21 ]. EpsK was reported to play an important role in polysaccharide biosynthesis, however, its exact function has not been characterized [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we found that B. licheniformis CGMCC 2876 could produce polysaccharides and γ-PGA under different culture conditions [ 21 ]. EpsK was reported to play an important role in polysaccharide biosynthesis, however, its exact function has not been characterized [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…After the fermentation process, the biopolymer was extracted and purified using the method described in a previous study [ 21 ]. The content of total carbohydrates in the biopolymer was detected using the phenol–sulfuric acid method.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the polysaccharide content secreted by strain SK1-7 under an insoluble potassium source was higher than that under a soluble potassium source. The expression of the epsB gene was significantly upregulated with the addition of an insoluble potassium source, and it was upregulated 9.55 times at 10 h. epsB is the key gene regulating extracellular polysaccharide synthesis ( Elsholz et al, 2014 ; Liu et al, 2017 ). When cultured to the later growth of bacteria, it began to secrete a large amount of EPSs, which has a certain adhesion and can be used as an intermediate medium between potassium bacteria and mineral particles to bond them together to form a bacterial-mineral complex.…”
Section: Discussionmentioning
confidence: 99%
“…The mutant with improved EPS production demonstrated that the specific activities of phosphoglucomutase (5.4.2.2), UDP-glucose pyrophosphorylase (2.7.7.9) and UDP-galactose-4-epimerase (5.1.3.2) were higher than those of the wild-type strain 4951 , indicating potential targets for improvement of EPS production in strain WSUCF1 through homologous overexpression. The expression level of enzymes associated with GDP-mannose synthesis may also be important since multiple interventions during NDP-sugar synthesis are more likely to be efficient to promote EPS production 52,53 . As the second stage for EPS biosynthesis, GTs are responsible for the assembly of activated NDP-sugars to the polysaccharide chain.…”
Section: Discussionmentioning
confidence: 99%